Emerging Role of Corticosteroid-Binding Globulin in Glucocorticoid-Driven Metabolic Disorders - Moisan, Marie-Pierre; Castanon, Nathalie (Frontiers in Endocrinology, 2016)
Glucocorticoid hormones (GCs) are critical for survival since they ensure energy supply necessary to the body in an ever challenging environment. GCs are known to act on appetite, glucose metabolism, fatty acid metabolism and storage. However, in order to be beneficial to the body, GC levels should be maintained in an optimal window of concentrations. Not surprisingly, conditions of GC excess or deficiency, e.g. Cushing’s syndrome or Addison’s disease are associated with severe alterations of energy metabolism. Corticosteroid Binding Globulin (CBG), through its high specific affinity for GCs, plays a critical role in regulating plasma GC levels. Genetic studies in various species including humans have revealed that CBG is the major factor influencing inter-individual genetic variability of plasma GC levels, both in basal and stress conditions. Some, but not all of these genetic studies have also provided data linking CBG levels to body composition. The examination of CBG-deficient mice submitted to hyperlipidic diets unveiled specific roles for CBG in lipid storage and metabolism. The importance of CBG is even more striking when animals are submitted to high-fat diet combined to chronic stress, mimicking our occidental lifestyle. An influence of CBG on appetite has not been reported but remains to be more finely analyzed. Overall, a role of CBG in GC-driven metabolic disorders is emerging in recent studies. Although subtle, the influence of CBG in these diseases could open the way to new therapeutic interventions since CBG is easily accessible in the blood.